Extracellular DNA: A Nutritional Trigger of Mycoplasma bovis Cytotoxicity - Zhu, Xifang; Dordet-Frisoni, Emilie; Gillard, Lucie; Ba, Abou; Hygonenq, Marie-Claude; Sagné, Eveline; Nouvel, Laurent Xavier; Maillard, Renaud; Assié, Sébastien; Guo, Aizhen; Citti, Christine; Baranowski, Eric (Frontiers in Microbiology, 2019)
Microbial access to host nutrients is a key factor of the host-pathogen interplay. With their nearly minimal genome, wall-less bacteria of the class Mollicutes have limited metabolic capacities and largely depend on host nutrients for their survival. Despite these limitations, host-restricted mycoplasmas are widely distributed in nature and many species are pathogenic for humans and animals. Yet, only partial information is available regarding the mechanisms evolved by these minimal pathogens to meet their nutrients and the contribution of these mechanisms to virulence. By using the ruminant pathogen Mycoplasma bovis as a model system, extracellular DNA (eDNA) was identified as a limiting nutrient for mycoplasma proliferation under cell culture conditions. Remarkably, the growth-promoting effect induced by supplementation with eDNA was associated with important cytotoxicity for actively dividing host cells, but not confluent monolayers. To identify biological functions mediating M. bovis cytotoxicity, we produced a library of transposon knockout mutants and identified three critical genomic regions whose disruption was associated with a non-cytopathic phenotype. The coding sequences (CDS) disrupted in these regions pointed towards pyruvate metabolism as contributing to M. bovis cytotoxicity. Hydrogen peroxide was found responsible for eDNA-mediated M. bovis cytotoxicity, and non-cytopathic mutants were unable to produce this toxic metabolic compound. In our experimental conditions, no contact between M. bovis and host cells was required for cytotoxicity. Further analyses revealed important intra-species differences in eDNA-mediated cytotoxicity and H2O2 production, with some strains displaying a cytopathic phenotype despite no H2O2 production. Interestingly, the genome of strains PG45 and HB0801 were characterized by the occurrence of insertion sequences (IS) at close proximity to several CDSs found disrupted in non-cytopathic mutants. Since PG45 and HB0801 produced no or limited amount of H2O2, IS-elements might influence H2O2 production in M. bovis. These results confirm the multifaceted role of eDNA in microbial communities and further identify this ubiquitous material as a nutritional trigger of M. bovis cytotoxicity. M. bovis may thus take advantage of the multiple sources of eDNA in vivo to modulate its interaction with host cells, a way for this minimal pathogen to overcome its limited coding capacity.